2021
DOI: 10.1108/mrr-05-2020-0286
|View full text |Cite
|
Sign up to set email alerts
|

Arresting fake news sharing on social media: a theory of planned behavior approach

Abstract: Purpose This study aims to examine the collective impact of awareness and knowledge about fake news, attitudes toward news verification, perceived behavioral control, subjective norms, fear of missing out (FoMO) and sadism on social media users’ intention to verify news before sharing on social media. Design/methodology/approach The current study’s conceptual framework is developed by a comprehensive literature review on social networking and the theory of planned behavior. The data for samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 176 publications
2
34
1
1
Order By: Relevance
“…This conceptual paper has studied the practices of entrepreneurial education dimension toward the elements of the Theory of Planned Behaviour which has never been done in Indonesia and is in line with the thoughts of previous researchers who suggested that the dimensions of entrepreneurial education should be implemented in different countries (Rengiah & Sentosa, 2016;Farid & Rahman, 2020;Kaki et al, 2022). In addition, the results of previous studies (Pundir, Devi, & Nath, 2021;Hadi, Sentosa, & Ab Wahid, 2022) also proposed adding other variables in order to enrich the body of knowledge from the Theory of Planned Behaviour.…”
Section: Discussionsupporting
confidence: 63%
“…This conceptual paper has studied the practices of entrepreneurial education dimension toward the elements of the Theory of Planned Behaviour which has never been done in Indonesia and is in line with the thoughts of previous researchers who suggested that the dimensions of entrepreneurial education should be implemented in different countries (Rengiah & Sentosa, 2016;Farid & Rahman, 2020;Kaki et al, 2022). In addition, the results of previous studies (Pundir, Devi, & Nath, 2021;Hadi, Sentosa, & Ab Wahid, 2022) also proposed adding other variables in order to enrich the body of knowledge from the Theory of Planned Behaviour.…”
Section: Discussionsupporting
confidence: 63%
“…Implementation of deterrence messages plays an important role with regard to copyright infrigements (Rooij et al , 2017). Similarly, awareness about the need to be alert about fake news can be spread through campaigns under the Digital India scheme (Pundir et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Marketers need to manage how consumer data is transacted and handled (Martin, 2020). For example, social media companies operating in India need to sensitize users in India about the importance of verifying online news before sharing (Pundir et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media sites have given people globally an unprecedented chance to start sharing knowledge and information, but they have also created a situation in which false information can be propagated just as quickly (Alkhateri et al, 2021). Several research have been conducted related to fake news sharing and Pundir et al, (2021) suggested that demographics and cultural variations can be used as moderator factors in future study to better understand false news spreading behaviour.…”
mentioning
confidence: 99%